THE EFFECT OF DISCOVERY LEARNING MODEL ON LEARNING OUTCOME OF GRADE-VII STUDENTS OF SMPN 5 NANGAPANDA - Kristina Herliana Inde; Melkyanus B.U. Kaleka; Ilyas Ilyas (Universitas Negeri Yogyakarta, 2020)
The study aimed to determine the effect of discovery learning models on learning outcomes of grade-VII students of SMPN 5 Nangapanda in the academic year 2019/2020. The type of research was survey research with a quantitative approach that used ex-post facto research designs. The population in this study was students of grade-VII of SMPN 5 Nangapanda, and the sample was 27 students obtained by purposive sampling technique. Data obtained from the study sample in the form of daily test scores on science subjects. The data analysis technique was performed by a one-sample t-test. The results showed the discovery learning model affects the learning outcomes of science students in grade-VII of SMP 5 Nangapanda in the academic year 2019/2020. This finding was indicated by the results of data analysis for science learning outcomes with the sig level. 0.05 and 95% confidence level, so that the sig obtained. 0.115 greater than 0.05.